Detrital zircon U–Pb ages of the Murui Formation in the Zhalantun area: Implications for the Early Cretaceous tectonic setting of the southern Great Xing'an Range, NE China. (17th January 2018) - Han, Xiaomeng; Zheng, Changqing; Han, Yubao; Xu, Xuechun; Shi, Lu; Xu, Jiulei; Li, Juan
Abstract : This paper reports U–Pb ages of detrital zircons from a series of clastic and pyroclastic rocks from the Murui Formation in the southern Great Xing'an Range (GXR), NE China, with the aim of constraining the depositional age of this poorly dated unit. These data, combined with the petrographic and sedimentology characteristics of the rocks, are used to constrain the sediment sources and tectonic setting of the provenance and provide wider insight into the tectonic evolution of the southern GXR during the Late Mesozoic. Two lithic arkose samples have dominant age groups at 249–250, 159–160, 136–147, and 394–415 Ma, and 301–323, 278–288, 209–237, and 142–163 Ma, respectively. The U–Pb zircon data constrain the maximum depositional age of the Murui Formation to 136 ± 1 Ma, that is, the Early Cretaceous. A lithic–crystal tuff from the upper Murui Formation yielded zircons with a weighted mean U–Pb age of 136 ± 1 Ma ( n = 47, mean square weighted deviation (MSWD) = 2.2), indicating that volcanic activity was contemporaneous with sedimentation of the Murui Formation. U–Pb dating of zircons from a pyromeride in the Baiyingaolao Formation that was erupted unconformably onto the Murui Formation yielded a peak age of 120 Ma, which constrains the depositional age of the Murui Formation to 120–136 Ma. Further dating of detrital zircons shows a range of ages, indicating the various of sediment origins. The Late Jurassic to Early Cretaceous volcanic rocks in the GXR served as the principal detrital sources for the Murui Formation in the southern GXR. Grain size and modal analysis of the sediments shows that the depositional environment was a stable intracontinental fluvial setting, and the provenance of the detritus was most likely a magmatic arc. According to stratigraphic contact relations, the Baiyingaolao Formation is supposed to have obvious intervals with lower volcanic strata, which combined with disparities between the southern and northern GXR in terms of the duration of volcanism, magmatic events, and the depositional age of the Murui Formation. We can conclude that the restricted occurrence of the Early Cretaceous detritus between the earlier and later phases of volcanism suggests progressive exhumation of the southern GXR in the Early Cretaceous. These may relate to post‐orogenic extension related to oceanic subduction. The southern GXR remained a site of active sedimentation during the continental extension period across the whole of NE China in the Late Jurassic to Early Cretaceous.